175. A preliminary study on the correlation of modulation plan parameters with dosimetric accuracy of VMAT treatment plans performed in two centres with different linear accelerators and treatment planning systems. (December 2018) - de Fatis, P. Tabarelli; Vacchieri, I.; Palleri, F.; Liotta, M.; Argazzi, E.; Ciarmatori, A.; Lappi, S.
Abstract: Purpose: To evaluate a correlation between plan parameters and Γ passing rate that could predict dosimetric accuracy of VMAT treatment plans. Methods: Ten pelvis treatment plans (irradiation of prostate, seminal vesicles and pelvis nodes with simultaneous integrated boost technique) have been performed on the same CT series and contoured structure sets in Istituti Clinici Scientifici Maugeri (ICSM) and in Azienda Ospedaliera Ospedali Riuniti Marche Nord (AORMN). Two 6 MV VMAT beams have been planned with Philips Pinnacle3 v16 (ICSM) and Elekta Monaco v 5.11(AORMN) for Varian Clinac iX® with Millenium MLC® 120-leaves and Elekta Synergy® with MLCi2 80 leaves respectively. The total prescribed dose has been 70.2 Gy in 26 fractions. The same planning criteria have been followed in both centres; the dose constraints on OARs (in particular peritoneal cavity) had been always achieved and preferred to the PTV coverage. RTPlan files were analyzed with Matlab® to obtain MUs and plan parameters used to calculate MCS, average Leaf Travel (LT) and their combination (LTMCS) whose definition is found in literature[1] . Local, global and normalized to dose prescription Γ index (3%, 3 mm) enabled the comparison between calculated and measured dose on the PTW Octavius 4D® volume phantom. The Pearson coefficient between Γ passing rate values and all the considered parameters has been computed to looking for a correlation. Results: Pearson coefficients are shown in Table 1 for all the parameters and Γ passing rate considered. The correlation is always strong for MU and moderate for all Γ indexes against MCS for ICSM and for the two Γ global indexes for Pesaro against MCS and LTMCS (Table 1). Conclusions: The results show a strong correlation against MU for both centres that could be useful to predict VMAT dosimetric accuracy expressed as Γ passing rate.